(untitled) (Revista Contexto & Educação, 2025)
This article analyzes the role of translation and the mother tongue in learning a modern foreign language, focusing on vocabulary acquisition of the target language using technological resources, such as Generative Artificial Intelligence, exemplified by ChatGPT. The research proposes a pedagogical approach inspired by Paulo Freire, aiming at the cultural integration of the student in the modern foreign language and the promotion of innovative education, based on the ethical use of technologies. The investigation aims to observe how students in a public school in Distrito Federal deal with the meaning of words, both individually and in relation to sentence context, and whether they can learn and grasp the target language in a way similar to the natural acquisition of their mother tongue, using Generative Artificial Intelligence critically and without plagiarism. Translation activities, the use of online bilingual dictionaries, and ChatGPT are resources employed in this process. The study is situated within a public education context that values the exchange of experiences in the international scenario and seeks critical, emancipatory, and decolonizing education. The qualitative research, with bibliographical, documentary, and empirical approaches, was conducted through interviews and participant observation in a public school in Distrito Federal. The conclusions highlight the importance of translation in building the target language lexicon, the effectiveness of proper use of Generative Artificial Intelligence and bilingual dictionaries, and the appreciation of the mother tongue, promoting the students’ sociocultural and ethical development.